Diffuse aspiration bronchiolitis: analysis of 20 consecutive patients - Xiaowen Hu (Jornal Brasileiro de Pneumologia, 2015)
OBJECTIVE: Aspiration can cause a variety of pulmonary syndromes, some of which are not well recognized. The objective of this study was to assess the demographic, clinical, radiological, and histopathological correlates of diffuse aspiration bronchiolitis (DAB), a bronchiolocentric disorder caused by recurrent aspiration. METHODS: This was a retrospective study of 20 consecutive patients with DAB seen at the Mayo Clinic in Rochester, Minnesota, between January 1, 1998 and June 30, 2014. RESULTS: The median age of the patients was 56.5 years (range, 22-76 years), and the male/female ratio was 2.3:1.0. In 18 patients, the diagnosis of DAB was based on the results of a lung biopsy; in the 2 remaining patients, it was based on clinical and radiological features, together with documented aspiration observed in a videofluoroscopic swallow study. In 19 patients (95%), we identified predisposing factors for aspiration, including gastroesophageal reflux disease (GERD), drug abuse, and dysphagia. Common presenting features included cough, sputum production, dyspnea, and fever. Twelve patients (60%) had a history of recurrent pneumonia. In all of the patients, chest CT revealed bilateral pulmonary infiltrates consisting of micronodules and tree-in-bud opacities. In the majority of patients, interventions aimed at preventing recurrent aspiration (e.g., anti-GERD therapies) led to improvement in the symptoms of DAB. CONCLUSIONS: Young to middle-aged subjects with recognizable predisposing factors for aspiration and who report a history of recurrent pneumonia are at increased risk for DAB. Although DAB is not well recognized, certain chest CT features are characteristic of the disorder.